The Relationship Of Partner Attention With Parenting Stress In Parents Who Have Early Children - Tio Heriyana (Universitas Muhammadiyah Kuningan, 2021)
This study aims to determine whether there is a relationship between partner attachment and parenting stress in parents who have aged children. The hypothesis proposed is that there is a negative relationship between partner attachment and parenting stress in parents who have early childhood. The research subjects were couples who had early childhood who were taken by accidental sampling technique. Data collection was carried out using a scale and scale for future optimism through a questionnaire. The data analysis technique used is the product moment correlation. Based on the results of the analysis, it was found that the significance value was 0.339> 0.05 and the degree of relationship was 0.097, so it was stated that there was no correlation between variables.